A current study of psychological well-being in educational institutions: A systematic literature review - Mukhlis, Hamid; Hariri, Hasan; Riswandi, Riswandi; Haenilah, Een Yayah; Sunyono, Sunyono; Maulina, Dina; Fitriadi, Fitriadi (Intelektual Pustaka Media Utama, 2024)
The issue of psychological well-being in education has emerged as an increasingly critical topic in recent years. This is due to the significance of psychological well-being in enhancing the performance of e ducational institutions, encompassing students, teachers, and the process of formulating school policies. This study sought to discover recent research on psychological well-being from an academic perspective. A total of 27 research articles were successfully gathered and reviewed based on the established criteria. This article review was conducted utilizing two databases (SCOPUS and WoS) and the following keywords: